2016
DOI: 10.1002/jbmr.2913
|View full text |Cite
|
Sign up to set email alerts
|

Novel Genetic Variants Associated With Increased Vertebral Volumetric BMD, Reduced Vertebral Fracture Risk, and Increased Expression of SLC1A3 and EPHB2

Abstract: Genome-wide association studies (GWASs) have revealed numerous loci for areal bone mineral density (aBMD). We completed the first GWAS meta-analysis (n = 15,275) of lumbar spine volumetric BMD (vBMD) measured by quantitative computed tomography (QCT), allowing for examination of the trabecular bone compartment. SNPs that were significantly associated with vBMD were also examined in two GWAS meta-analyses to determine associations with morphometric vertebral fracture (n = 21,701) and clinical vertebral fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 58 publications
0
36
0
4
Order By: Relevance
“…Simply measuring X-ray attenuation expressed as Hounsfield units (HU) to derive BMD has been evaluated (62,63), but ideally the tissue density of the analyzed volume is calibrated to units of equivalent concentration of a hydroxyapatite phantom in g/cm 3 yielding the BMD values (64). Volumes of interest are defined and a distinction is made between cortical, trabecular and integral volumes (65).…”
Section: Computed Tomography (Ct)mentioning
confidence: 99%
“…Simply measuring X-ray attenuation expressed as Hounsfield units (HU) to derive BMD has been evaluated (62,63), but ideally the tissue density of the analyzed volume is calibrated to units of equivalent concentration of a hydroxyapatite phantom in g/cm 3 yielding the BMD values (64). Volumes of interest are defined and a distinction is made between cortical, trabecular and integral volumes (65).…”
Section: Computed Tomography (Ct)mentioning
confidence: 99%
“…rs17040773 is not in linkage disequilibrium with rs10190845 in our population (r 2 =0.006), and in keeping with this, when we performed conditional analysis on rs17040773, we confirmed that rs10190845 remained significantly associated with clinical vertebral fractures (P=2.09×10 −8 ; OR 1.73 (95% CI 1.43 to 2.09)). In order to test whether the variants associated with clinical vertebral fractures played a role in BMD, we tested the rs10190845 variant for association with volumetric vertebral BMD in females on the dataset from Nielson and colleagues 27. We did not find any association for the variant and BMD (P=0.23).…”
Section: Resultsmentioning
confidence: 92%
“…We also analysed 15 variants previously associated with clinical fracture,13 of which three were associated with clinical vertebral fractures in this study. We also analysed the SNPs identified by Nielson and colleagues27 as genome-wide significant predictors of volumetric vertebral BMD for association with clinical vertebral fractures in our dataset. Of the six genome-wide significant SNPs identified by Nielson et al , we found that one was significantly associated with clinical vertebral fractures after Bonferroni correction (rs12742784, P=6.24×10 −5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nielson and colleagues took a different approach to exploring the genetics of spinal endophenotypes (5) . They performed a classical GWAS using CT quantification of lumbar spine vBMD, with specific focus on 'pure' trabecular bone, adjusting for age, gender and weight.…”
Section: Lumbar Spinal Volumetric Bmd; Novel Genetic Variantsmentioning
confidence: 99%
“…Though the sample size (around 2000) was insufficient to perform a GWAS, they were able to gain important insights into genetic influences by examining the heritability of spinal curvature, and its genetic correlation with other traits (4) . In contrast, Nielson et al, assembled over 15,000 participates, making it feasible to perform a GWAS, from which novel loci were identified which have not previously been found in GWAS of DXA-derived lumbar BMD (5) .…”
Section: Introductionmentioning
confidence: 99%